Rapid molecular assay for the evaluation of clove essential oil antifungal activity against wheat common bunt - Valente, Maria Teresa; Orzali, Laura; Manetti, Giuliano; Magnanimi, Francesco; Matere, Antonio; Bergamaschi, Valentino; Grottoli, Alessandro; Bechini, Sara; Riccioni, Luca; Aragona, Maria (Frontiers in Plant Science, 2023)
Common bunt of durum wheat (DW), Triticum turgidum L. ssp. durum (Desf.) Husn., is caused by the two closely related fungal species belonging to Tilletia genus (Tilletiales, Exobasidiomycetes, Ustilaginomycotina): Tilletia laevis Kühn (syn. T. foetida (Wallr.) Liro.) and Tilletia caries (DC) Tul. (syn. Tilletia. tritici (Bjerk.) G. Winter). This is one of the most devastating diseases in wheat growing areas worldwide, causing considerable yield loss and reduction of quality of wheat grains and flour. For these reasons, a fast, specific, sensitive, and cost-effective method for an early diagnosis of common bunt in wheat seedlings is urgent. In this study, a TaqMan Real Time PCR- based method was developed for rapid diagnosis and quantification of T. laevis in young wheat seedlings, before tillering stage. The high sensitivity, detecting up to 10 fg of pathogen DNA, specificity, and robustness of the assay, allowed to directly analyze the crude plant extract. This method, along with phenotypic analysis, was used to study conditions favoring pathogen infection. The results showed that temperature represented a critical point for disease development when using wheat seeds contaminated by T. laevis spores, and low temperatures were required in the first seedling development stages for the success of infection. The molecular method developed was also used for evaluating the effectiveness of clove oil-based seed dressing in controlling the disease. It was able to quantify T. laevis in young wheat seedlings after seed dressing by clove oil in different formulations and ways of application (spray and submersion), greatly reducing analysis times. In conclusion, clove oil dressing could represent a promising tool for managing wheat bunt especially in sustainable farming. Finally, the Real Time PCR-based method developed could also represent a useful tool to speed up the tests of genetic breeding for disease resistance.